Calculation of Structural Reliability of Main Gas Pipelines Using Modern Software Application - Nagizade, A.R.; Ismayılova, F.B. (Herald of Azerbaijan Engineering Academy, 2023)
In the article, the issue of pipeline thickness calculation with methods based on modern technologies is considered. According to the coefficient of working conditions of the pipeline, the calculated resistance to tension (compression) is determined and the thickness of the pipe is calculated based on the obtained result. Also, as a result of the calculation of the pipe elements, the stressdeformation state is analyzed along the surface of the pipeline where the technical inspection is carried out. During the calculations, both the analytical method and modern software are used. A threedimensional spatial model of the pipeline is built through the software, and a report on the strength and stability of the pipeline under the influence of a number of forces is conducted. Also, as a result of the technical diagnostics of the pipeline, the possibility of future operation of the pipe element is determined.